SOCIO-ECONOMIC DRIVERS OF FOOD SECURITY AMONG SMALLHOLDER RURAL HOUSEHOLD MAIZE FARMERS IN IDO LOCAL GOVERNMENT AREA OF OYO STATE, NIGERIA - Oladeji, S.O.; Olatunji, A.T.; Jamiyu, A.G.; Ibirogba, O.R.; Ogunola, A.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined the socio-economic drivers of food security among smallholder rural household maize farmers in Ido Local Government of Oyo State, Nigeria. Primary data was used to collect information from One hundred and twenty (120) respondents. Data were analyzed using descriptive statistics, Households’ food consumption expenditure approach (HFE) and logistic regression model. The results revealed that majority (71.67%) of the respondents were male which implies that farming in the study area was pre- dominantly concentrated by male. Majority (65.83%) of the respondents were married while 70.83% of the respondent were between the age brackets of 41 years and above with an average age of 54 years. The results of the logistic regression indicates that, household size was negatively significant at (p<0.001) showing the larger the household size, the more likelihood of the farm households to be food insecure. The distribution of mean weekly household expenditure classified by budget item shows that food accounted for the bulk of the expenditure (74.69%). Education, clothing, healthcare and drugs, transportation and other items like recharge card, kerosene, etc. accounted for the remaining 25.31%. Farm size owned by the respondents was significant at (p<0.05) and had positive relationship with food security status of households. Both access to credit and access to extension service were positive significant (p<0.05) in influencing food security status of the farming household in the study area. Coping strategies included relying on support from family, selling assets, reducing food consumption, and facing challenges such as insufficient farm size and limited access to credit and extension services. The study concluded that, age, gender, farm size, marital status, access to credit, and household size were identified as the significant determinants of food security of maize farming households in the study area. The study recommended that, improving farmers' access to micro-credit, supported by both governmental and non-governmental organizations, is essential for overcoming resource acquisition challenges and the government should provide assistance to extension agencies disseminating agricultural technologies as well as promoting family planning initiatives to address large family sizes as a barrier to achieving food security.